2017
DOI: 10.1590/1516-3180.2016.021921102016
|View full text |Cite
|
Sign up to set email alerts
|

Association of risk factors with smoking during pregnancy among women of childbearing age: an epidemiological field study in Turkey

Abstract: CONTEXT AND OBJECTIVE: Smoking during pregnancy is an important risk factor for maternal and infant health that is preventable. This study aimed to investigate the risk factors associated with smoking behavior during pregnancy. DESIGN AND SETTING: A household-based probability sample survey of 1,510 women was conducted in the center of the city of Sivas, Turkey, between September 2013 and May 2014. METHODS: The prevalence of smoking during pregnancy was estimated according to independent variables by mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
3
5
0
2
Order By: Relevance
“…Conversely, women who did (vs. did not) successfully quit smoking during pregnancy were more than 4 times more likely to be highly educated. These findings are in line with previous studies [21,23,[25][26][27]34] and emphasize that more attention is needed to help women with a lower educational level to quit smoking before and during pregnancy.…”
Section: Discussion/conclusionsupporting
confidence: 92%
See 1 more Smart Citation
“…Conversely, women who did (vs. did not) successfully quit smoking during pregnancy were more than 4 times more likely to be highly educated. These findings are in line with previous studies [21,23,[25][26][27]34] and emphasize that more attention is needed to help women with a lower educational level to quit smoking before and during pregnancy.…”
Section: Discussion/conclusionsupporting
confidence: 92%
“…A large study focusing on smoking before pregnancy found that women who did not take folic acid, who had a low educational level, who had an unplanned pregnancy, and who lived alone were more likely to smoke before pregnancy [21]. Other studies found that women who were younger [22][23][24], were unmarried, or lived alone [21,23,25], had a low educational level [21][22][23][24][25][26], lived in an extended family [23], did not take folic acid [21], and had partners who smoked [25] were more likely to smoke during pregnancy. In addition, women were more likely to quit smoking during pregnancy when they were married [27], had a higher socioeconomic status [22], had a higher educational level [27][28][29], lived with a non-smoking cohabitant [27,29], and smoked fewer cigarettes before pregnancy or quitting [27].…”
Section: Introductionmentioning
confidence: 99%
“…The association of some individual factors on maternal smoking behavior has already been reported in previous studies [7,12,[19][20][21]23,24]. Although most previous studies were conducted in Western countries, similar results in this Japanese study suggest that these factors are not affected by the living environment or ethnic differences.…”
Section: Discussionsupporting
confidence: 86%
“…We excluded questions with too many options (15 options exist on question 10). We also excluded questions that would not have a direct effect on maternal smoking behavior (13)(14)(15)(16), based on previous studies [7,[9][10][11][12][13][14][17][18][19][20][21][22][23][24][25][26][27][28]. Finally, we selected 9 questions (1-9) as individual variables.…”
Section: Exposure Variablesmentioning
confidence: 99%
“…Factors associated with nicotine dependence during pregnancy are: aged under 25 years old, low level of education, unmarried and living in extended families (Nur, 2017). A systematic review reported similar findings where women of younger age, have low social status, a large number of children, without a partner or living with a partner who smokes, and deficient prenatal care, are more likely to smoke than other women (Schneider & Schütz, 2008).…”
Section: Introductionmentioning
confidence: 85%